POSTOPERATIVE COMPLICATIONS IN DIABETIC INDIVIDUALS HAVING ORTHOPEDIC AND GENERAL SURGERY - ABBASI , SH; ASIM , A; SARFRAZ , M; BASHIR , MA; KANWAL , S; IMTIAZ , H (Biological and Clinical Sciences Research Journal, 2023)
It is not fully understood why diabetic patients tend to have worse clinical outcomes following surgery. A recent study aimed to identify the variables that contribute to negative outcomes in diabetic patients who undergo planned orthopedic or general surgery. The study analyzed data from the Al Nafees Medical College and Hospital Islamabad and included 500 patients with diabetes who underwent surgery between February 2022 to August 2022. Of these patients, 48 percent had orthopedic surgery, while 52 percent had general surgery. The average age of the patients was 64.6 ±11.82, and the average length of diabetes diagnosis was 8.91±7.64. After the surgery, 40 patients (8%) experienced negative outcomes, including delayed extubation in 17 patients (42.5%), circulatory disorder in 4 patients (10.0%), respiratory abnormalities in 6 patients (15.0%), non-healing of the incision in 5 patients (12.5%), infections at other sites in 4 patients (10.0%), other complications in 3 patients (7.5%), and death in 1 patient (2.5%). The study used multivariable logistic regression to identify the factors associated with postoperative negative outcomes. The results revealed that patients who were over 65 years old had a higher chance of negative outcomes [odds ratio (OR)=2.33, 95% confidence interval (CI): (1.26,3.88)]. Other factors that contributed to negative outcomes were impaired kidney function (OR=2.53, 95% CI: 1.33-6.58), diabetes complications (OR=2.63, 95% CI: (1.56, 4.68), male sex (OR=2.24; 95% CI: (1.34, 3.48), and general surgery (OR=1.68; 1.61, 5.46; 95% CI: (1.61, 5.46). In conclusion, higher age, male sex, high postoperative blood glucose levels, diabetic-related complications, impaired kidney function, and the type of surgical procedure contributed to postoperative negative outcomes in diabetic patients who undergo planned surgery.